VENOUS CEREBRAL INFARCTION AFTER REMOVAL CONVEXITAL MENINGIOMAS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The article presents a case from the practice of developing venous infarction of the brain after removal of convexital meningioma. This complication is of great interest due to the ambiguity of the pathophysiological processes in the development of postoperative venous infarction of the brain